Clinical laboratory shadowing- an elective program in undergraduate health professions training: perception, strengths and challenges - Vineetha K. Ramdas Nayak; Prajna P. Shetty; Vaideki Balamurugan; Vijetha Shenoy Belle; Ravindra Maradi; Kirtana R. Nayak (BMC Medical Education)
Abstract Background The authors aim to evaluate the perception, strengths, and challenges in the implementation of “Clinical Laboratory Shadowing” as an elective module for third-year professional medical students. Methods Clinical Laboratory shadowing is an elective module designed by the faculty of Biochemistry for Phase III part-2 medical students. The elective comprises modules explaining the functioning of the Biochemistry Laboratory in a hospital. The students are provided insights into the different processes involved in laboratory testing. They are taught about total quality management of the Biochemistry Laboratory. Thirteen students from Batch 2019 and eight students from Batch 2020 volunteered to attend the elective. Students’ feedback regarding the learning was analyzed with the help of a questionnaire. Pre-test and post-test questions were evaluated to test the knowledge gained during the elective. Two focus group discussions were conducted regarding the benefits and areas for improvement for the elective. Results Following the elective module there was a significant improvement in the test score compared to baseline. A majority (84–95%) of students perceived that the shadowing elective was well planned, and materials were well prepared, there was appropriate engagement with the facilitators, gained knowledge on the principles of total quality management, good laboratory practices, disease process, and diagnosis. Most (53–74%) of the students felt that this elective was not monotonous and not difficult. Around 84–95% of students felt that this elective module enhanced the importance of interprofessional communication and teamwork. Moreover, through focused group discussions, several recurring themes emerged. Among these, the scope for improvement within the module is profound. The faculties were of the opinion that the shift from conventional training to competency-based learning was effectively embraced by the students, underscoring the importance of consistent small group activities in the module to enhance the skills of Good laboratory practices. The students expressed a desire for additional clinical correlation and interpretation classes in the elective module, showing their preference for student-centred clinically oriented learning. Conclusion The current study concludes that including an elective module on Clinical laboratory shadowing is an overall positive experience for medical students in enhancing their knowledge of basic sciences and application of the concepts in diagnosing cases. This elective may be desirable to adopt in other medical colleges in India.